The Role of Corporate Marketing Communications Management in Implementing Advertising Ethics and Standards - Bambang Adi Wijaya; M. Noveriady; Noormarizqa Puspaningratri; Syahrial Shaddiq (Institute of Computer Science (IOCS), 2021)
Australia’s advertising industry has dramatically improved during the last ten years, including the quality of ethical code, number of associations as advertising watchdog, creative ideas and the executions as well. Advertising agencies become vital as brands or companies start using their services not only to execute the advertising, but also to develop the whole campaign, such as using Public Relations approach. That’s what integrated marketing communication is all about: to elaborate advertising, Public Relations, sales promotion and direct marketing approach into a whole, integrated campaign. However, the implementation of the campaign is not as simple as it looks due to the complexity of the process. In this case, Smarties and its brand umbrella, Nestle Australia, has developed a massive national campaign called “Eight Colors of Fun”. It turns into a disaster when local communities and watchdog associations have complained its TV commercial